Perancangan Aplikasi Presensi Karyawan Berbasis Mobile Dengan Qrcode Dan Otentikasi Biometrik - Nur Muhamad Rizalul Fahmi; Siti Marlina; Yoseph Tajul Arifin (LPPM Universitas Bina Sarana Informatika, 2022)
The level of performance can be assessed through the level of attendance of employees of a company, attendance is one of the parameters in evaluating employee performance. Several companies or government agencies will always maximize facilities in supporting their work activities, including the employee attendance system. Unfortunately, not all agencies or companies can implement the system properly. Some of them still use the traditional way of recording attendance. This of course can cause some problems both in terms of users or data management, especially if the number of users who make attendance is very large. In addition to data management problems, other problems such as an authentication system that is less secure and prone to fraud can occur. The purpose of this study is to design and implement an android application to make it easier for users to carry out the presence process that is installed on registered devices with the support of scanning a QR code that is generated randomly for each session with biometric authentication support to ensure only verified users run the application. Based on the statement, the application of application-based presence can speed up users in carrying out the presence process with just a few steps, and increase security and user validation.